Comisionar la verdad y la memoria en la sociedad - Gabriel Ruiz Romero; Marije Hristova (Colombia Internacional, 2019)
This article analyses the political function assumed by a truth commission, as an entity situated at the center of disputes regarding memory typical of societies dealing with a violent past. The text proposes that rather than the construction of the truth, the main function of a truth commission is the promotion and consolidation of a new regime of truth that opposes that which has been constructed through a violent past. Analyzing the Colombian case, the article critically examines the concept of reconciliation, which underlies the work of a commission of this type, as a mechanism of transitional justice. We propose that the truth commission avoids the promotion of a national reconciliation, understood as a pact to hide the violent past behind an insurmountable wall that steers us away from assuming responsibility and consequences in the present. Instead, the article sets out that the truth commission must promote reconciliation within society; that is, a process that seeks to preserve certain communicating vessels with a violent past, in that it addresses the causes that propitiated the emergence and naturalization of this violence. Methodology: The study was guided by the Gadamerian premise of questioning one’s own certainties. Based on experience in research in the area of memory, and on the researchers own experience in the production of official historic memory reports, what underlies this article is a hermeneutic work of general enquiry into the functions of memory in transition periods, and, in particular, into the challenges faced by a truth commission. Conclusions: The article concludes that the central task of a truth commission is not so much the recovery of specific memories (this happened in this way), but rather the construction of the social framework for the legitimation of the memory of suffering. This requires an effort to incorporate the suffering in society’s general representation, its needs, and its values. In this sense, although described as an instrument for seeking the truth, the real social and political purpose of the truth commission may be its capacity to build a new regime of truth that opens a present space through which to understand the current patterns of violence and recognize its current agents. The article also concludes, about the Colombian case, that the Commission for the Clarification of the Truth, Coexistence, and Non-Repetition should function as an enabler of a narrative public sphere. In this order of ideas, it must create frameworks of meaning in which to unfold counter-hegemonic narratives that may even become bothersome in social terms. It is about opening up a possibility for different social agents traditionally situated at the margins of the State, to take a position from which to dialogically confront the State itself and the groups that have sought to impose their narrative through armed command or control of the public sphere. Originality: The boom of such studies on memory in the second half of the twentieth century has meant that the topic has been approached from many disciplines and perspectives within the social sciences. Ours is a hermeneutic approach that does not attempt to account for the contents of memory or the nature of the truth produced in the institutionalised work of memory; rather, it situates its analysis among the possibilities for the development of a space for the narrative resonance in which it is possible to produce an alternative regime of truth.